Traditional Chinese Medicine and Colorectal Cancer: Implications for Drug Discovery - Qiang Sun; Man He; Meng Zhang; Sha Zeng; Li Chen; Hui Zhao; Han Yang; Maolun Liu; Shan Ren; Haibo Xu (Frontiers Media S.A., 2021)
As an important part of complementary and alternative medicine, traditional Chinese medicine (TCM) has been applied to treat a host of diseases for centuries. Over the years, with the incidence rate of human colorectal cancer (CRC) increasing continuously and the advantage of TCM gradually becoming more prominent, the importance of TCM in both domestic and international fields is also growing with each passing day. However, the unknowability of active ingredients, effective substances, and the underlying mechanisms of TCM against this malignant tumor greatly restricts the translation degree of clinical products and the pace of precision medicine. In this review, based on the characteristics of TCM and the oral administration of most ingredients, we herein provide beneficial information for the clinical utilization of TCM in the prevention and treatment of CRC and retrospect the current preclinical studies on the related active ingredients, as well as put forward the research mode for the discovery of active ingredients and effective substances in TCM, to provide novel insights into the research and development of innovative agents from this conventional medicine for CRC treatment and assist the realization of precision medicine.